Significant increase in natural disturbance impacts on European forests since 1950 - Patacca, Marco; Lindner, Marcus; Lucas-Borja, Manuel Esteban; Cordonnier, Thomas; Fidej, Gal; Gardiner, Barry; Hauf, Ylva; Jasinevičius, Gediminas; Labonne, Sophie; Linkevičius, Edgaras; Mahnken, Mats; Milanovic, Slobodan; et al. (Global change biology, 2023)
Over the last decades, the natural disturbance is increasingly putting pressure on European forests. Shifts in disturbance regimes may compromise forest functioning and the continuous provisioning of ecosystem services to society, including their climate change mitigation potential. Although forests are central to many European policies, we lack the long-term empirical data needed for thoroughly understanding disturbance dynamics, modeling them, and developing adaptive management strategies. Here, we present a unique database of >170,000 records of ground-based natural disturbance observations in European forests from 1950 to 2019. Reported data confirm a significant increase in forest disturbance in 34 European countries, causing on an average of 43.8 million m3 of disturbed timber volume per year over the 70-year study period. This value is likely a conservative estimate due to under-reporting, especially of small-scale disturbances. We used machine learning techniques for assessing the magnitude of unreported disturbances, which are estimated to be between 8.6 and 18.3 million m3 /year. In the last 20 years, disturbances on average accounted for 16% of the mean annual harvest in Europe. Wind was the most important disturbance agent over the study period (46% of total damage), followed by fire (24%) and bark beetles (17%). Bark beetle disturbance doubled its share of the total damage in the last 20 years. Forest disturbances can profoundly impact ecosystem services (e.g., climate change mitigation), affect regional forest resource provisioning and consequently disrupt long-term management planning objectives and timber markets. We conclude that adaptation to changing disturbance regimes must be placed at the core of the European forest management and policy debate. Furthermore, a coherent and homogeneous monitoring system of natural disturbances is urgently needed in Europe, to better observe and respond to the ongoing changes in forest disturbance regimes.
Keywords: forest natural disturbances; Trees; empirical disturbance data; Forests; Ecosystem; fire; lesy; stromy; windstorms; zvířata; Europe; Coleoptera; climate change; bark beetles; European forests; brouci; Animals; Evropa; ekosystém